2014
DOI: 10.1039/c4cc02596b
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrothiophenes containing quaternary stereogenic centres by sequential stereospecific rearrangements and ring-closing metathesis

Abstract: Stereospecific [3,3]-sigmatropic rearrangement of O-substituted thiocarbamate derivatives of enantiopure allylic alcohols provides allylic thiocarbamates as single enantiomers. Intramolecular arylation by rearrangement of their allyllithium derivatives provides allylic tertiary thiols. Allylation and ring-closing metathesis gives 2,5-dihydrothiophenes containing sulfur-bearing quaternary centres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…6 For tertiary thiols, 7 Hoppe's thiocarbamate chemistry, [8][9][10][11][12][13][14] despite its attendant limitations of electrophiles, and the enantioselective palladium-catalyzed sigmatropic rearrangement of O-allyl thiocarbamates developed by Overman, are effective. 15 We recently reported some effective methods for the enantioselective synthesis of tertiary thiols based on lithiation/aryl migration sequences of S-benzyl- 16 and S-allyl 17,18 N-arylthiocarbamates (Scheme 1). The methods involve the generation of enantiomerically enriched configurationally stable organolithiums by deprotonation of chiral non racemic S-benzyl or S-allyl N-arylthiocarbamates: the organolithiums undergo stereospecific aryl migration 19 from the thiocarbamate N atom to the C atom α to S. In parallel, in the racemic series, we showed that the Li-coordinating abilities of the thiocarbamate group 8,11 could be exploited for a connective stereoselective synthesis of thiols by a diastereoselective carbolithiation of S-alkenyl groups followed by intramolecular N to C migration of an aryl moiety.…”
Section: Introductionmentioning
confidence: 99%
“…6 For tertiary thiols, 7 Hoppe's thiocarbamate chemistry, [8][9][10][11][12][13][14] despite its attendant limitations of electrophiles, and the enantioselective palladium-catalyzed sigmatropic rearrangement of O-allyl thiocarbamates developed by Overman, are effective. 15 We recently reported some effective methods for the enantioselective synthesis of tertiary thiols based on lithiation/aryl migration sequences of S-benzyl- 16 and S-allyl 17,18 N-arylthiocarbamates (Scheme 1). The methods involve the generation of enantiomerically enriched configurationally stable organolithiums by deprotonation of chiral non racemic S-benzyl or S-allyl N-arylthiocarbamates: the organolithiums undergo stereospecific aryl migration 19 from the thiocarbamate N atom to the C atom α to S. In parallel, in the racemic series, we showed that the Li-coordinating abilities of the thiocarbamate group 8,11 could be exploited for a connective stereoselective synthesis of thiols by a diastereoselective carbolithiation of S-alkenyl groups followed by intramolecular N to C migration of an aryl moiety.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the synthetic utility of obtained allyl sulfides was exemplified in an intramolecular ring‐closing methathesis reaction. The adduct of allyl mercaptan was transformed to a chiral 2‐substituted dihydrothiophene19b, 21 in modest yield (Scheme ). Among the tested RCM catalysts, a modified Hoveyda–Grubbs catalyst (Green‐cat)22 offered the best yield of the cyclic product.…”
Section: Resultsmentioning
confidence: 99%
“…281) [726]; (2) cyclic phosphonates fused to benzene or heteroaromatic rings [727]; (4) dihydrothiophenes (e.g. 282) [728]; (5) alkenylsultones (e.g. 283) in a process involving simultaneous formation of an unsaturated lactone from a tetraene precursor [729]; (6) aromatic ring fused sultones (e.g.…”
Section: )mentioning
confidence: 99%
“…A more stable osmabenzene was formed by replacing the chloride ligands with thiocyanate ligands. Key events in this transformation involve hydroxide elimination to form the cyclic carbene complex(727), which undergoes ring opening to afford the allenylphosphonium salt(728). Addition of chloride to the vinylphosphonium salt group followed by elimination of triphenylphosphine affords the osmabenzene.…”
mentioning
confidence: 99%